Si quantum dots enhancement stimulated Raman scattering of water molecules. (20th November 2018) - Li, Fabing; Wang, Ying; Li, Zhanlong; Fang, Wenhui; Li, Yeqiu; Sun, Chenglin; Men, Zhiwei
Abstract: Stimulated Raman scattering (SRS) spectra of the OH stretching vibrations of pure water and 2‐nm Si quantum dots (Si QDs) water solution have been investigated under different pump laser energies. Simultaneously, we have studied the spontaneous Raman spectra of pure water and Si QDs water solution at room temperature and atmospheric pressure. The results show that SRS intensity of Si QDs water solution is an order of magnitude higher than that of pure water at the same laser energy, which indicates that Si QDs enhance the SRS intensity of water molecules. The QDs enhancement SRS mechanism is attributed to the increase of third‐order nonlinear Raman susceptibility from the electric fields induced by the exciton effect of Si QDs. Abstract : Stimulated Raman scattering (SRS) intensity of Si quantum dots (Si QDs) water solution is an order of magnitude higher than that of pure water. The increase of the third‐order nonlinear polarizability in water molecules is induced from the exciton effect of Si QDs. Due to Si QDs having a self‐absorption effect, the most obvious enhancement effect appears at laser energy of 110 mJ.